ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI: KEPUTUSAN TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR DI BEI - ., Stephanie; ., Sistomo; Simanjuntak, Ramot P. (Fundamental Management Journal, 2017)
Influence of Taxes, Foreign Ownership and The Size of the Company to Transfer Pricing. This research aims to determine the influence of taxes, foreign ownership, and the size of the company against the decision of transfer pricing on manufacturing companies listed in Indonesia Stock Exchange (BEI). The data used in this research is secondary data sample company for the last five years from 2011 to 2015. The research method used is a quantitative data method using multiple linear regression model to test the hypothesis that has been made. The results showed that the tax has a positive effect on transfer pricing, foreign ownership has positive effect on transfer pricing, and the size of the company negatively affect transfer pricing. The results also showed that there are significant effect between taxes, foreign ownership and the size of the company together to transfer pricing.Key word : transfer pricing, tax, foreign ownership, the size of the company.